Obesity in the HIV-infected population in Northeast England: a particular issue in Black-African women. (March 2017) - Ilozue, C; Howe, B; Shaw, S; Haigh, K; Hussey, J; Price, DA; Chadwick, DR
People living with HIV are surviving longer on successful antiretroviral therapy and obesity rates are increasing. We sought to determine the prevalence of being overweight or obese in a regional population of people living with HIV and to explore the demographic and clinical characteristics associated with obesity or being overweight. Data on patients attending three Northeast England clinics were collected including body mass index and demographics. The prevalence of being overweight (body mass index ≥ 25 kg/m 2 ) or obese (body mass index ≥ 30 kg/m 2 ) was determined and compared with regional population data. Associations between being overweight or obese and demographic and other data were further explored using logistic regression models. In 560 patients studied (median age 45 years, 26% Black-African and 69% male), 65% were overweight/obese and 26% obese, which is similar to the local population. However, 83% and 48% of Black-African women were overweight/obese or obese, respectively, with 11% being morbidly obese (body mass index > 40 kg/m 2 ). In the multivariate analyses, the only factors significantly associated with obesity were Black-African race (adjusted odds ratio 2.78, 95% confidence interval 1.60–4.85) and type 2 diabetes (adjusted odds ratio 4.23, 95% confidence interval 1.81–9.91). Levels of obesity and overweight in people living with HIV are now comparable to the levels in the local population of Northeast England; however, the prevalence is significantly higher in Black-African women. Given the additional risk factors for cardiovascular disease inherent in people living with HIV, better strategies to prevent, identify and manage obesity in this population are needed.